Development and Testing of a Passive Ankle Exoskeleton - Pardoel, Scott (Université d'Ottawa / University of Ottawa, 2017)
Aging is accompanied by a deterioration of physical abilities. For some this limits their mobility and thus their quality of life. Exoskeletons are a class of walking assist device that help reduce the effort required to walk. Currently, powered exoskeletons suffer from short battery life and thus limited usefulness. This thesis presents the design, fabrication, and testing of a novel unpowered ankle exoskeleton to assist normal walking over long distances. The design incorporates a Pneumatic Artificial Muscle (PAM) inflated and used as a passive air spring. To predict the behaviour of the PAM in this distinct application, a distinct dynamic model was developed to include the biaxial stress in the bladder as well as a polytropic gas assumption. Experimental testing was used to validate the model and indicated that the addition of the bladder stress enhanced the performance of the force prediction at low pressure but had negligible impact on the model at higher pressures. The experimental testing also showed that the temperature of the gas inside the PAM varies very slightly during passive elongation cycles, thus, validating an isothermal assumption. Once fabricated, the exoskeleton was tested in human walking trials. Electromyography results showed that the exoskeleton was able to reduced the muscular activation activation of the Soleus muscle, however the results also included a significant reduction in the angular range of motion of the ankle. This is thought to be attributed to an insufficient acclimatization period during the human testing. Furthermore, due to an improper fit of the exoskeleton, the clutch mechanism did not operate as designed, leading to a reduced range of motion of the ankle. The device demonstrated its ability to reduce the effort of the calf muscles during walking, however, further refinements of the device fitting and clutch mechanism are required.
Keywords: PAM; Exoskeleton; Walking; Passive